Distributed KDC-Based Random Pairwise Key Establishment in Wireless Sensor Networks. (19th July 2010) - Su, Zhong; Jiang, Yixin; Ren, Fengyuan; Lin, Chuang; Chu, Xiaowen
Abstract : Key management is a core mechanism to provide secure and reliable communications in wireless sensor networks (WSNs). In large-scale WSNs, due to the resource constraint on sensor nodes, it is still an extremely challenging task to achieve good performance in terms of high network connectivity and strong resilience against sensor nodes capture with low overheads. To address this issue, in this paper we propose a novel random pairwise key establishment scheme, called RPKE. In RPKE, sensor nodes differentiate their roles as either auxiliary nodes or ordinary nodes prior to network deployment. The auxiliary nodes act as distributed key distribution center (KDC), and neighboring ordinary nodes can establish pairwise key with the help of the distributed KDC. Theoretical analysis and simulation evaluation demonstrate that RPKE performs well in terms of network connectivity and resilience at the cost of low computation/communication/storage overheads, compared to the existing counterparts.